Hashimoto's thyroiditis and secondary hypertension - Jandrić-Kočić Marijana (Association of Nurses Technicians and Midwives, 2019)
INTRODUCTION: Hashimoto's is a chronic autoimmune inflammatory process of the thyroid gland that is characterized by autoantibody formation, lymphocytic infiltration and destruction of glandular tissue while reducing its function. It is a significant and often unrecognized cause of secondary arterial hypertension resulting from an increase in atrial resistance, a decrease in cardiac contractility, a decrease in glomerular filtration rate, abnormal sodium metabolism, activation of the sympathetic nervous system and endothelial dysfunction. CASE REPORT: A patient born in 1952 arrives at a family medicine clinic because of 24-hour ambulatory blood pressure monitoring (ABPM) indicated by a cardiologist as part of the evaluation of exacerbation of previously stable hypertension. In regular therapy, he uses: Enalapril 20 mg 1x1, Enalapril hydrochlorothiazide 10/25 mg 1x1, Indapamide 2.5 mg 1x1, Simvastatin 10 mg 1x1, Levothyroxine natrium 50 mcg 1x1 / 2. ABPM verifies elevated daily, night and 24h average outpatient blood pressure, a significant increase in blood pressure in the morning and during intense physical activity. The ultrasound examination shows a significant increase in the size of the thyroid gland compared to the earlier findings, while laboratory processing detects hypothyroidism. Patients are referred to the Department of Nuclear Medicine where total thyroidectomy is indicated. One month after surgery, the patient uses Levothyroxine natrium 100 mcg 1x1 for 6 days and 1x3 / 4 on the seventh day, while initial antihypertensive therapy is limited to Enalapril 5 mg 1x1. CONCLUSION: Early detection and adequate substitution therapy for Hashimoto's thyroiditis allows for normalization or significant reduction in the value of secondary hypertension, reducing the possibility of irreversible changes in blood vessels and coexisting essential hypertension.